New strategies for the treatment of inflammatory bowel diseases. (May 2013) - Roblin, Xavier; Dronne, William; Paul, Stéphane; Tedesco, Emilie Del
Anti-TNF therapy is the most important treatment for inflammatory bowel disease patients. However, primary nonresponders are frequent and clinical recurrence under maintenance therapy is reported in 40% of the treated patients. The aim of this article is to explain the most important targets for the future of treatments in inflammatory bowel disease and to report the results of these news drugs in clinical practice. Two Phase III studies clearly indicate the interest of golimumab and vedolizumab in induction and maintenance treatment for ulcerative colitis patients. Soon it will be possible to analyze the principal regulation defect in each patient to design a more personalized treatment. Before this step, it is important first to try to optimize treatment and then to consider a switch to another drug.